Computational Simulation of the Electronic State Transition in the Ternary Hexagonal Compound BaAgBi - Chang, Yu; Wang, Xin; Na, Sanggyun; Zhang, Weiwei (Frontiers in Chemistry, 2021)
Topological properties in metals or semimetals have sparked tremendous scientific interest in quantum chemistry because of their exotic surface state behavior. The current research focus is still on discovering ideal topological metal material candidates. We propose a ternary compound with a hexagonal crystal structure, BaAgBi, which was discovered to exhibit two Weyl nodal ring states around the Fermi energy level without the spin–orbit coupling (SOC) effect using theoretical calculations. When the SOC effect is considered, the topological phases transform into two Dirac nodal line states, and their locations also shift from the Weyl nodal rings. The surface states of both the Weyl nodal ring and Dirac nodal lines were calculated on the (001) surface projection using a tight-binding Hamiltonian, and clear drumhead states were observed, with large spatial distribution areas and wide energy variation ranges. These topological features in BaAgBi can be very beneficial for experimental detection, inspiring further experimental investigation.